2008
DOI: 10.1029/2007gl032681
|View full text |Cite
|
Sign up to set email alerts
|

Temporary vegetation disturbance as an explanation for permanent loss of tidal wetlands

Abstract: [1] Coastal ecosystems respond to sea level and sediment supply change according to complex, three-way interactions between vegetation, hydrology, and sediment transport. While biogeomorphic feedbacks preserve the morphology of intertidal surfaces covered by marshland, we demonstrate with numerical model and field experimentation that temporary disturbance to vegetation facilitates rapid and widespread degradation. Vertical accretion slows in disturbed areas, allowing localized submergence of the marsh platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 19 publications
9
84
0
Order By: Relevance
“…The Black Bank site is 17 cm below MHW. It has been shown in mesocosms and model simulations that a natural feedback of marsh vegetation to low elevation is increased aboveground production and stem elongation, which traps mineral and organic particulates and adds plant litter to the surface, contributing to vertical accretion (Morris et al 2002, Kirwan et al 2008, Mudd et al 2009. The diameters of the rhizomes were significantly larger at the Black Bank site, perhaps to support the increased aboveground biomass in the waterlogged, mucky soils.…”
Section: Other Anthropogenic Impacts On the Jamaica Bay Estuarymentioning
confidence: 94%
See 1 more Smart Citation
“…The Black Bank site is 17 cm below MHW. It has been shown in mesocosms and model simulations that a natural feedback of marsh vegetation to low elevation is increased aboveground production and stem elongation, which traps mineral and organic particulates and adds plant litter to the surface, contributing to vertical accretion (Morris et al 2002, Kirwan et al 2008, Mudd et al 2009. The diameters of the rhizomes were significantly larger at the Black Bank site, perhaps to support the increased aboveground biomass in the waterlogged, mucky soils.…”
Section: Other Anthropogenic Impacts On the Jamaica Bay Estuarymentioning
confidence: 94%
“…Deegan et al (2012) reported fracturing and slumping of the creek-bank edge and a corresponding increase in fine organic matter in tidal channels associated with the fertilized marsh creek. Sediment erosion from one portion of a marsh system (e.g., creek-bank edge, tidal channel) can be a source of sediment to a surviving marsh area, thereby contributing to vertical accretion (Kirwan et al 2008). …”
Section: Marsh Elevation and Changes In Peat Compositionmentioning
confidence: 99%
“…Elevation relative to mean sea level is a critical variable for the establishment and maintenance of biotic coastal communities and a threat to biodiversity (Kirwan & Murray 2008b, Kirwan et al 2008, as has been detected in the past for the Basque Country (Pascual & Rodríguez-Lázaro 2006). In tidal areas, this elevation determines the duration and frequency at which coastal habitats are submerged, this being one of the factors controlling the productivity of macrophyte communities (Morris et al 2002).…”
Section: Sea Level Rise and Estuarine Habitatsmentioning
confidence: 99%
“…An increase in mean sea level induces a higher risk of the flooding of low-lying coastal areas, erosion of sandy beaches and barrier island coasts, intrusion of saltwater and the loss of wetlands, amongst other effects (Wolanski & Chappell 1996, Morris et al 2002, Crooks 2004, Pascual & Rodríguez-Lázaro 2006, FitzGerald et al 2008, Kirwan & Murray 2008a, Kirwan et al 2008, Poulter & Halpin 2008, Gesch 2009). These climate-change-driven threats will probably exacerbate several existing pressures along the coastal regions such as the concentration of population (McGranahan et al 2007) and the increasing rate of urbanisation (European Environment Agency 2006), causing degradation, fragmentation and habitat loss (Fahrig 2003, Halpern et al 2008.…”
Section: Coastal Floodingmentioning
confidence: 99%
“…Particularly relevant are marshes situated on coastal platforms in the intertidal range for which minor changes in topography and hydrodynamics can lead to vegetation disturbance and thus cause rapid marsh degradation [34]. The general deepening of the delta relative to mean sea level and the gentler slope of the coastal platform in the modelled deltas for higher SLR along with a change in flow velocity range (Figure 3) may well have significant implications for coastal marsh survival.…”
Section: Dynamic Delta Reponse To Slrmentioning
confidence: 99%